Manajemen Pengembangan Karakter Muslim Moderat Pada Siswa Madrasah Aliyah - Musta'in Ahmad; Giyoto Giyoto; Rochmat Budi Santoso (ITB AAS INDONESIA Surakarta, 2021)
The study of the concept of religious moderation in Islam or moderate Islam that has attracted the attention of Muslim scholars in fields of study such as socio-politics, Islamic education, language, and socio-religion. These terms are the meanings of various meanings used to label Muslims such as Modernist, Reformed and progressive Islam. This study aims to look at the management of moderate Muslim character among Islamic school students. The implementation of this research was conducted at Madrasah Aliyah Negeri 2 Surakarta. The methodology in this study uses a qualitative approach. Techniques of studying data in this study are observation, interviews and documentation. The method used to check the validity of the data is the triangulation method. Data analysis in this study used qualitative analysis. The results showed that the management of moderate Muslim character development in madrasah aliyah students at Madrasah Aliyah Negeri 2 Surakarta was carried out with several things that could make the character of the students able to understand and appreciate every difference, namely 1) Implementation of the curriculum in Madrasah Aliyah Negeri 2 Surakarta Islam. moderate is given in several subjects, especially subjects related to religious morals and morals such as PAI, Akidah Akhlak and several other subjects. 2) Madrasah Aliyah Negeri 2 Surakarta, there are several forms of integration related to moderate or moderate understanding of Islam in religion which is always applied in the madrasa environment, including through the learning process delivered by each teacher in the classroom, then through the process of understanding that has been realized. by Madrasah Aliyah Negeri 2 Surakarta through the culture in madrasah and the understanding that has been applied through various extracurricular activities.